106k views
1 vote
TRUE OR FALSE: FOR ANY FUNCTION, X=F^-1(Y), THEN Y=F(X). PLEASE EXPLAIN

User Lubna
by
5.4k points

1 Answer

3 votes

Answer:

True.

Explanation:

For example let f(x) = 3x + 1 then f-1(x) is found as follows

Let f(x) = y = 3x + 1 then

3x = y - 1

x = (y-1) / 3

x = f-1(x) = (x - 1)/3.

So:

Replacing the x in y by (x - 1)/3 :-

x = f(-1)(y) = ( (3x + 1) - 1) / 3

= 3x / 3

= x.

So y = f(x).

User Nithin Michael
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.